Syntactic Character of Cholpon's Poetry (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
This article analyzes the syntactic features of Cholpon's poetry. Also, special attention is paid to the fact that one of the criteria that determines the poetic skill of the creator is determined by the syntactic organization of the poetic speech. Reasonable opinions and comments are given throughout the article.